2018
DOI: 10.1371/journal.pone.0206652
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid thyroid autoantibodies, thyrotropin, free thyroxine levels and assisted reproductive technology outcome

Abstract: ObjectiveAlthough there are substantial data linking thyroid autoimmunity (TAI) and infertility, data regarding assisted reproductive technology (ART) outcomes and TAI markers in follicular fluid (FF) of women undergoing ART are scarce. Objective of the study was to assess the association of the levels of thyroid autoantibodies in FF and ART outcome expressed as the achieved pregnancies.MethodsThis study enrolled 52 women undergoing ART (26 TAI positive subjects and 26 age and body mass index matched TAI negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…The fact that when analyzing the four selected parameters in the IVF protocols, definitive conclusion about the effect of antithyroid antibodies and subclinical hypothyroidism on ART outcomes cannot be made, worth attention. For instance, Zhong et al [11] reported lower fertilization rate, implantation rate and pregnancy rate following IVF-ET in women with TAI, while Medenica et al [10] did not reveal any decrease in fertilization rate. Perhaps because in their group of subjects, some women also underwent ICSI treatment.…”
Section: Ivf/icsi Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…The fact that when analyzing the four selected parameters in the IVF protocols, definitive conclusion about the effect of antithyroid antibodies and subclinical hypothyroidism on ART outcomes cannot be made, worth attention. For instance, Zhong et al [11] reported lower fertilization rate, implantation rate and pregnancy rate following IVF-ET in women with TAI, while Medenica et al [10] did not reveal any decrease in fertilization rate. Perhaps because in their group of subjects, some women also underwent ICSI treatment.…”
Section: Ivf/icsi Outcomesmentioning
confidence: 98%
“…Pregnancies rates per initiated cycle and per embryo-transfer cycle were significantly different between the TAI positive and the TAI negative group (30.8% versus 61.5%), p ¼ .026 and (34.8% versus 66.7%), p ¼ .029, respectively. Multivariate analysis showed that TAI positive women had significantly less chance to achieve pregnancy (OR 0.036, 95% CI [0.004-0.347], p ¼ .004) [10].…”
Section: Introductionmentioning
confidence: 99%
“…T hyroid hormones (TH) may interact directly with oocyte physiology via the presence of TH receptors in granulosa/cumulus cells and indirectly by facilitating the actions of the follicle stimulation hormone (FSH) on granulosa cells in terms of the steroidogenic activity, cellular morphology, the expression of the LH/CG receptor, and by protecting them against apoptosis via the PI3-K pathway (1)(2)(3). Thyrotropin (TSH) receptors are also present on human ovarian tissue and granulosa cells, but their function needs to be investigated further (4).TH and thyroid antibodies are present in follicular fluid (FF) in concentrations that correlate with those in the serum, and recently, it has been suggested that thyroid peroxidase (TPO) might be present in granulosa cells (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies published since the 2017 ATA Guidelines, no alteration of the Guidelines are indicated, but further investigation is warranted. Five studies examined the association between thyroid autoimmunity and outcomes of ART (46)(47)(48)(49)(50). Two studies reported a negative association between thyroid autoimmunity and outcomes after ART (48)(49)(50).…”
Section: C) Autoimmunity and Preterm Delivery (Question 19)mentioning
confidence: 99%
“…Five studies examined the association between thyroid autoimmunity and outcomes of ART (46)(47)(48)(49)(50). Two studies reported a negative association between thyroid autoimmunity and outcomes after ART (48)(49)(50). In a retrospective cohort study of 300 However, three studies reported no difference in ART outcomes between women with and without thyroid autoimmunity (46,47).…”
Section: C) Autoimmunity and Preterm Delivery (Question 19)mentioning
confidence: 99%